2012
DOI: 10.1021/nl303619s
|View full text |Cite
|
Sign up to set email alerts
|

A Truncated Manganese Spinel Cathode for Excellent Power and Lifetime in Lithium-Ion Batteries

Abstract: Spinel-structured lithium manganese oxide (LiMn(2)O(4)) cathodes have been successfully commercialized for various lithium battery applications and are among the strongest candidates for emerging large-scale applications. Despite its various advantages including high power capability, however, LiMn(2)O(4) chronically suffers from limited cycle life, originating from well-known Mn dissolution. An ironical feature with the Mn dissolution is that the surface orientations supporting Li diffusion and thus the power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
201
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(220 citation statements)
references
References 35 publications
14
201
1
4
Order By: Relevance
“…The corresponding improvements in capacity retention at end-of-test (EOT), over cells with the baseline separator, are 75%, 90% and 125%, respectively for poly-BPA, poly-PEI and Na 4 EDTA. 64 The faradaic efficiency (FE) of all cells with chelating separators is also higher than FE of baseline cells. Furthermore, the FE for the baseline cells steadily decreases during the second half of the cycling test at 55…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding improvements in capacity retention at end-of-test (EOT), over cells with the baseline separator, are 75%, 90% and 125%, respectively for poly-BPA, poly-PEI and Na 4 EDTA. 64 The faradaic efficiency (FE) of all cells with chelating separators is also higher than FE of baseline cells. Furthermore, the FE for the baseline cells steadily decreases during the second half of the cycling test at 55…”
Section: Discussionmentioning
confidence: 99%
“…Some of the proposed mitigation measures demonstrate great ingenuity and technical virtuosity, but may have limited effectiveness and be of little practical utility due to cost considerations. For example, while controlling the crystal facets at the surface of active materials during synthesis 64 appears as an elegant and intellectually appealing mitigation measure for Mn dissolution, this only reduces and does not eliminate the Mn dissolution, at a cost which is unlikely to match that of the polycrystalline materials used in mass-produced batteries, which the have various crystals planes at the active material particle surfaces.…”
Section: A6316mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] However, there are several drawbacks of LMO including a severe capacity fade during cycling due to a Jahn-Teller (JT) distortion in the oxide material, as well as dissolution of Mn in the electrolyte. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Since the dissolution can initiate from the surfaces of LMO particles, a complete understanding of the surface structure and stability is the key to suppress the Mn loss and to overcome the current limitations of the spinel LMO as a Li-ion battery cathode. [2][3][4]11,12 The electrochemical performance of batteries with LMO cathodes depends on multiple factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…), and in particular, the morphology of the LMO particles obtained with different synthesis conditions can lead to diverse electrochemical properties. [5][6][7] For example, Kim et al demonstrated that the octahedron-shaped LMO cathode particles dominated by (111) surfaces exhibit a superior capacity retention compared to the platelet-shaped LMO dominated by (001) surface. 7 These findings suggest that the (111) LMO surface is more resistant to Mn dissolution, while other surfaces such as (001) are more likely to be more prone to it.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to graphite, TiO 2 has a higher lithium intercalation potential (1.75 V vs. Li + /Li), enabling it to avoid the deposition of metallic lithium, and it has higher capacity for Li + intercalation/de-intercalation [4,5]. [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%